Angioarchitectural alterations in the retina and choroid in frontotemporal dementia. - Ariana Allen; Cason B Robbins; Suzanna Joseph; Angela Hemesat; Anita Kundu; Justin P Ma; Alice Haystead; Lauren Winslow; Rupesh Agrawal; Kim G Johnson; Andrea C Bozoki; Sandra S Stinnett; et al. (PLoS ONE, 2024)
Objective Frontotemporal dementia (FTD) is a progressive neurodegenerative disorder that affects the frontal and temporal lobes of the brain, leading to cognitive decline and personality changes. The objective of this cross-sectional study was to characterize angioarchitectural changes in the retina and choroid of individuals with FTD compared to cognitively normal controls using optical coherence tomography (OCT) and OCT angiography (OCTA). Methods Cross-sectional comparison of patients with FTD and controls with normal cognition. All participants underwent Mini-Mental State Examination (MMSE) at the time of imaging. Outcome measures included OCT parameters: retinal nerve fiber layer (RNFL) thickness, ganglion cell layer-inner plexiform layer (GC-IPL) thickness, central subfield thickness (CST), subfoveal choroidal thickness (SFCT), choroidal vascularity index (CVI); and OCTA superficial capillary plexus parameters: foveal avascular zone (FAZ) area, 3x3mm and 6x6mm macular perfusion density (PD) and vessel density (VD), 4.5x4.5mm peripapillary capillary perfusion density (CPD) and capillary flux index (CFI). Generalized estimating equation analysis was used to account for the inclusion of 2 eyes from the same participant. Results 29 eyes of 19 patients with FTD and 85 eyes of 48 controls were analyzed. In FTD, 3x3mm macular PD (p = 0.02) and VD (p = 0.02) and CFI (p = 0.01) were reduced compared to controls. There was no difference in average 4.5x4.5mm CPD, RNFL thickness, GC-IPL thickness, CST, SFCT, CVI, FAZ, or 6x6mm VD or PD between FTD and controls (all p > 0.05); however, there was a trend toward lower macular 6x6mm PD and VD in patients with FTD. Conclusion Decline of peripapillary and macular OCT and OCTA parameters merit further investigation as potential biomarkers for FTD detection. Noninvasive retinal and choroidal imaging may hold promise for earlier detection, and future longitudinal studies will clarify their role in monitoring of FTD.